VORTEX FLOW INSIDE THE DEEP SPHERICAL DIMPLE - Воскобійник, В. (Proceedings of National Aviation University (archive), 2012)
The results of experimental researches of the forming features of the vortex flow which is formed at the turbulentflow above of the deep spherical dimple are presented. Visualization shows that inclined asymmetric large-scale vortices are generated inside the dimple. These vortex structures are switched from one tilt in other, exciting lowfrequencyoscillations. During an evolution the asymmetric vortices are broken up above an aft wall of the dimple andthe angle of their incline and break up is increased with the growth of Reynolds number.